Role of the PE/PPE Family in Host–Pathogen Interactions and Prospects for Anti-Tuberculosis Vaccine and Diagnostic Tool Design - Qian, Jianing; Chen, Run; Wang, Honghai; Zhang, Xuelian (Frontiers in Cellular and Infection Microbiology, 2020)
The pe/ppe genes are found in pathogenic and slow-growing Mycobacterium tuberculosis and other M. tuberculosis complex (MTBC) species. These genes have been suggested as key factors in host-pathogen interactions. Although the function of most PE/PPE family proteins is not fully understood, a growing body of evidence suggests that this protein family is involved in the pathogenesis of M. tuberculosis infection. In this review, we discuss the role of PE/PPE proteins, which are believed to be linked to the function of the ESX system. Further, we highlight the reported functions of PE/PPE proteins, including roles in host cell interaction, immune response regulation, and cell fate determination during complex host-pathogen processes. Finally, we propose future directions for PE/PPE protein research and consider how the current knowledge on these proteins might be applied for the design of more specific diagnostics and more efficient vaccines for global tuberculosis control.